Efektivitas Rosella Terhadap Penurunan Tekanan Darah pada Penderita Hipertensi - Suyamto; Sari Dian Nur Adkhana (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2013)
Background : Hypertension is the main problem of people’s health in Indonesia and in some parts of the world. Hypertension cannot recover by itself. The blood pressure tends to escalate as people are getting older. One of the cures is nonpharmacological, such as by following healthy life style. The other way is by curing it herbally, and one of them is consuming rosella flower sheath. Tujuan penelitian ini adalah untuk mengetahui efektivitas rosella terhadap penurunan tekana darah pada penderita hipertensi di Rt 3 dan Rt 4 Candikarang Sardonoharjo Ngaglik Sleman Yogyakarta. The research’s objective was to explore the efectiveness of rosella towards the decline of the blood pressure on hypertension sufferers in the Neighbourhood Community 3 and 4 Candikarang Sardonoharjo Ngaglik Sleman Yogyakarta. Aim of the Research: this research was aimed at identifying the rosella efectivenss towards the decline of the blood pressure on hypertension sufferers. Research Methodology : The research methodology which was applied here was the research design of pre experiemtnal one. The design of the research applied one group pretest-prostest, which was conducted in Candikarang Village, Sardonoharjo, Nganglik, Sleman, Yogyakarta from 3 May 2010 up to 17 May 2010 with the population of all 20 hypertension sufferers in the area and the samples were 11 people, using the acciental sampling tehcnique. Rosella was given in seven days respectively everyday as much as 10 grams mixed into 0,5 litre of water . the measuring tool to identify the respondents’ blood pressure during the pretest and posttest was using sphygmomanometer and sthetoscope. Result of the Research : Before the treatment was conducted, there was a person (9%) with hypertension, 4 people (36%) suffering from stadium I hypertension, and the rest, 6 people (55%) with stadium 2 hypertension. Aftter the treatement to the respondents’ blood pressur, there were 2 people (18%) having normal blood pressure, 1 person (9%) suffering from prehypertension, 2 people (18%) with stadium I hypertension, and the rest, 6 people (55%) suffering from stadium 2 hypertension. The analysis applied in this research was Wilcoxon to identify the difference between the blood pressure in the pretest postest treatment. Based on the statistical examination, the value of P was 0,194 which meant that the value of p > 0,05. It can be concluded that there was no effect of consuming rosella towards the decline of the blood pressure on the hypertension sufferers in the neighborhood community 3 and 4 Candikarang Village Sardonoharjo Ngaglik Sleman Yogyakarta. The suggestion for the next researchers is that they should prolong the time of the same research.